(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Commuting means waking up before the sun even rises just so you can avoid traffic. It means bracing yourself for the one-hour travel time- even without the traffic. Considering the high number of commuters, which exceeds the number of available public utility vehicles, as well as the terrible traffic, the very thought of commuting to any place is a nightmare. Despite the Factor our government is making efforts to improve our position, such as the development of “Bagong Jeeps” (BEEP), the current state of our public transportation is deplorable. As Filipinos are the ones who mainly use and facilitate these amenities, it can be said that the state of the Philippines’ public transport system is a representation of the Filipino. The lack of discipline that drivers have, which greatly contributes to the heavy flow of traffic, points back to how Filipinos unknowingly cause the problems that they continuously gripe about. The result of the study about the factors affecting the flow of traffic during rush hour in Barangay Tungko Mangga San Jose Del Monte as regards the road condition is that the average composite mean is 2.85 and interpreted as agreeable. As regards the volume of traffic, the average composite mean is 2.90 and interpreted as Agree. As regards the traffic enforcers’ availability, the average composite mean is 3.00 and interpreted as Agree. The respondents’ assessment of the factors affecting the flow of traffic is by utilizing the sidewalk, implementing no garage, no car policy, and utilizing pedestrian lanes and overpasses. There are some proposed recommendations to further enhance the factors affecting the flow of traffic during rush hour, which include improving intersections, using public transportation more than private transportation, and carpooling.